CHNQD-00603 Promotes Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells by the miR-452-3p-Mediated Autophagy Pathway - Xin, Shanshan; Li, Shao-Ming; Gao, Ling; Zheng, Jing-Jing; Wu, Yan-Wei; Shao, Chang-Lun; Ren, Wen-Hao; Zhi, Keqian (Frontiers in Cell and Developmental Biology, 2021)
Background: Periodontitis is a chronic and progressive disease accompanied by bone loss. It is still a challenge to restore the bone structure. The osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) plays a decisive role in bone restoration and regeneration. Marine natural products (MNPs) have multiple biological activities, including anti-tumor and anti-inflammatory properties. However, the exploration of MNPs in osteogenesis is far from sufficient. Methods: We obtained a series of derivatives through structural optimization from 4-phenyl-3,4-dihydroquinolin-2(1H)-one alkaloid isolated from Scopulariopsis sp. Some preliminary cytological experiments showed that CHNQD-00603, obtained by adding a methoxy group to the position C3 and a hydroxyl group to the position C4 of 4-phenyl-3,4-dihydroquinolin-2(1H)-one, might promote the osteogenic differentiation of BMSCs. To further investigate the effects of CHNQD-00603 on BMSCs, we performed a CCK-8 assay and qRT-PCR, alkaline phosphatase staining (ALP), and alizarin red S staining to assess the cytotoxicity and the ability of osteogenic differentiation of CHNQD-00603. The autophagy level was assessed and validated by WB, qRT-PCR, and transmission electron microscopy. Then, 3-methyladenine (3-MA) was added to further examine the role of autophagy. Based on the expression of autophagy-related genes, we predicted and examined the potential miRNAs by bioinformatics. Results: CCK-8 assay showed that CHNQD-00603 at 1 µg/ml did not influence BMSCs activity. However, the proliferation rate decreased from the seventh day. qRT-PCR, ALP staining, ALP activity assay, and Alizarin red S staining showed that the best concentration of CHNQD-00603 to promote osteogenic differentiation was 1 µg/ml. Further investigations indicated that CHNQD-00603 activated autophagy, and the inhibition of autophagy by 3-MA attenuated CHNQD-00603-enhanced osteogenic differentiation. Subsequently, the findings from bioinformatics and qRT-PCR indicated that miR-452-3p might be a regulator of autophagy and osteogenesis. Furthermore, we transfected BMSCs with miR-452-3p NC and mimics separately to further determine the function of miR-452-3p. The data showed that the overexpression of miR-452-3p moderated the level of autophagy and osteogenic differentiation of CHNQD-00603-treated BMSCs. Conclusion: Our data suggested that CHNQD-00603 promoted the osteogenic differentiation of BMSCs by enhancing autophagy. Meanwhile, miR-452-3p played a regulatory role in this process.